Analisis Wacana Persuasif Dalam Spanduk Yang Terdapat DiWilayah Kabupaten Wonogiri - Andreas, Riski, Drs. Agus Budi Wahyudi, M. Hum, Drs. Andi Haris Prabawa, M. Hum (2017)
Singer study aimed (1) to describe Shape persuasive discourse wilayah hearts banners in Wonogiri. (2) Classify Form persuasive discourse wilayah hearts banners in Wonogiri. Operates singer is descriptive qualitative research. Data collection hearts Research singer using techniques SIMAK, technical notes, methods of data analysis using method agih The tool that determining precisely Part Of Language The concerned ITU Alone, Research Singer (1) describe the Form Discourse persuasive hearts banners in the region of Wonogiri. (A). Persuasive suggestion amounted to 8 (b). persuasive inducements amounted to 2, (c). Orders persuasive numbered 13, and (d) .persuasif invitation amounted to 6; (2) classifies Form persuasive discourse hearts banners by Segi, Form persuasive From (a). Political terms amounted to 10 (b). Business terms (economic) amounted to 15 (c). In terms of health amounted to 2, (d). In terms of religion 1, and (e). Tourism in terms of the number 1.